The Cytoplasmic Domain of the SARS-CoV-2 Envelope Protein Assembles into a β-Sheet Bundle in Lipid Bilayers. Issue 5 (1st March 2023) - Dregni, Aurelio J.; McKay, Matthew J.; Surya, Wahyu; Queralt-Martin, Maria; Medeiros-Silva, João; Wang, Harrison K.; Aguilella, Vicente; Torres, Jaume; Hong, Mei
Graphical abstract: Highlights: The SARS-CoV-2 E protein is a viroporin with multiple functions. Membrane-bound E exhibits a β-sheet rich cytoplasmic domain. The E β-sheet bundle exists at high protein densities in low-curvature membranes. Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) envelope (E) protein forms a pentameric ion channel in the lipid membrane of the endoplasmic reticulum Golgi intermediate compartment (ERGIC) of the infected cell. The cytoplasmic domain of E interacts with host proteins to cause virus pathogenicity and may also mediate virus assembly and budding. To understand the structural basis of these functions, here we investigate the conformation and dynamics of an E protein construct (residues 8–65) that encompasses the transmembrane domain and the majority of the cytoplasmic domain using solid-state NMR. 13 C and 15 N chemical shifts indicate that the cytoplasmic domain adopts a β-sheet-rich conformation that contains three β-strands separated by turns. The five subunits associate into an umbrella-shaped bundle that is attached to the transmembrane helices by a disordered loop. Water-edited NMR spectra indicate that the third β-strand at the C terminus of the protein is well hydrated, indicating that it is at the surface of the β-bundle. The structure of the cytoplasmic domain cannot be uniquely determined from the inter-residue correlations obtained here due to ambiguities in distinguishing intermolecular and intramolecular contacts for a compact pentameric assembly of this small domain. Instead, we present four structural topologies that are consistent with the measured inter-residue contacts. These data indicate that the cytoplasmic domain of the SARS-CoV-2 E protein has a strong propensity to adopt β-sheet conformations when the protein is present at high concentrations in lipid bilayers. The equilibrium between the β-strand conformation and the previously reported α-helical conformation may underlie the multiple functions of E in the host cell and in the virion.